Apolipoprotein E genotypes and longevity across dementia disorders. Issue 7 (13th March 2018) - Skillbäck, Tobias; Lautner, Ronald; Mattsson, Niklas; Schott, Jonathan M.; Skoog, Ingmar; Nägga, Katarina; Kilander, Lena; Wimo, Anders; Winblad, Bengt; Eriksdotter, Maria; Blennow, Kaj; Zetterberg, Henrik
Abstract: Introduction: The ε4 allele of the apolipoprotein E ( APOE ) gene is a prominent risk factor for Alzheimer's disease (AD), but its implication in other dementias is less well studied. Methods: We used a data set on 2858 subjects (1098 AD, 260 vascular dementia [VaD], 145 mixed AD and VaD, 90 other dementia diagnoses, and 1265 controls) to examine the association of APOE polymorphisms with clinical dementia diagnoses, biomarker profiles, and longevity. Results: The ε4 allele was associated with reduced longevity as ε4 versus ε3 homozygotes lived on average 2.6 years shorter ( P  = .006). In AD, ε4 carriers lived 1.0 years shorter than noncarriers ( P  = .028). The ε4 allele was more prevalent in AD, mixed AD and VaD, and VaD patients compared to controls, but not in other dementia disorders. Discussion: The APOE ε4 allele is influential in AD but might also be of importance in VaD and in mixed AD and VaD, diseases in which concomitant AD pathology is common.